Nutritional status of patients with ataxia‐telangiectasia: A case for early and ongoing nutrition support and intervention. (6th February 2015) - Ross, Lynda J; Capra, Sandra; Baguley, Brenton; Sinclair, Kate; Munro, Kate; Lewindon, Peter; Lavin, Martin
<x xml:space="preserve">Abstract</x> Aim Ataxia‐telangiectasia (A‐T) is a rare genomic syndrome resulting in severe disability. Chronic childhood disorders can profoundly influence growth and development. Nutrition‐related issues in A‐T are not well described, and there are no nutritional guidelines. This study investigated the nutrition‐related characteristics and behaviours of Australian A‐T patients attending a national clinic. Methods A cross‐sectional analysis of 13 A‐T patients (nine females; aged: 4–23 years): nutritional status was assessed by anthropometric and body cell mass (BCM) calculations. Parents reported their child's diet history and physical and behavioural factors that affect nutrition including fatigue and need for assistance. Results Ten (77%) had short stature (height for age z scores <−1), and seven (54%) were underweight for height (weight/height z scores <−1). Significant malnutrition (BCM z scores <−2) was detected in nine (69%) including the one adult who was severely malnourished. Malnutrition increased significantly with age (BCM for height z scores and age, r = −0.937, P < 0.001). Eight (62%) patients ate poorly compared with estimated energy requirement for weight. Poor diet quality was characterised by high fat and sugar choices. Parents reported significant nutritional barriers as chronic tiredness and the need for care giver assistance with meals. Conclusions This study confirms profound malnutrition in Australian A‐T patients. Poor intakes and diet quality suggest the need for early nutrition intervention. Ongoing support for families and early discussions on tube feeding are required to address changing needs in childhood and likely nutritional decline into adulthood. A prospective study is required to assess feasibility and effectiveness of nutrition interventions in young people with A‐T.